Impact of Anthropometric Parameters on Peak Expiratory Flow Rate - Komal Atta; Sadaf Zia; Farkhanda Jabeen (Aziz Fatimah Medical and Dental College, 2019)
Objective: The aim of the study was to determine the variation of Peak Expiratory Flow Rate (PEFR) with various anthropometric measurements. Methodology: It was a cross sectional study conducted University Medical and Dental College Faisalabad from August 2019 to September 2019.The study comprised of 210 participants of age 18 to 25 years. A detailed history regarding smoking, respiratory disease and allergies were taken. Body mass index (BMI) was calculated from recorded height and weight. PEFR was measured by Peak flow meter. Data was analyzed by SPSS 21. Mean and SD was calculated for continuous variables. Percentages were estimated for categorical variables. ANOVA and t-test were used for comparison of mean between the groups. Association of PEFR with anthropometric measurements was analyzed by regression analysis. Results: Of total population of 210 subjects, 60.5% were males 39.5% were females. Mean PEFR was higher in tall than short heighted subjects. This difference was significant. (p value=0.005*). Significant difference in mean PEFR was also noted with respect to weight distribution of subjects (p value = 0.01*). On analyzing the subjects on the basis of BMI, we observed lower PEFR values in underweight and obese subjects in contrast to subjects with normal BMI, however this difference was not significant (p value = 0.42). PEFR was positively associated with height (p value = 0.004*) PEFR was not significantly associated with age, weight and BMI. Conclusion: PEFR was positively influenced by height and taller subjects have greater PEFR values than short heighted subjects. Age, weight and BMI have no impact on PEFR.